2018
DOI: 10.1177/1071100718790243
|View full text |Cite
|
Sign up to set email alerts
|

Prospective Evaluation of Utilization Patterns and Prescribing Guidelines of Opioid Consumption Following Orthopedic Foot and Ankle Surgery

Abstract: Level II, prospective observational cohort study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
74
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(78 citation statements)
references
References 37 publications
2
74
2
Order By: Relevance
“…Various studies have examined factors that might influence the amount of narcotic pain medication a patient might require after foot and ankle surgery. Saini et al 14 saw that increasing age was associated with less narcotic use. Mulligan et al 12 showed that a history of chronic pain, mood disorders, tobacco use, and preoperative narcotic use were all associated with increased postoperative narcotic use.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Various studies have examined factors that might influence the amount of narcotic pain medication a patient might require after foot and ankle surgery. Saini et al 14 saw that increasing age was associated with less narcotic use. Mulligan et al 12 showed that a history of chronic pain, mood disorders, tobacco use, and preoperative narcotic use were all associated with increased postoperative narcotic use.…”
Section: Discussionmentioning
confidence: 99%
“…11 Although many types of orthopedic procedures necessitate opioid prescriptions for pain management, foot and ankle surgeries are especially associated with elevated levels of opioid prescriptions. 10,14 Increased control of opioid prescription has been attempted on both clinical and regulatory levels. In North Carolina, the Strengthen Opioid Misuse Prevention Act of 2017 (STOP Act) went into effect on January 1, 2018, augmenting the efforts of established federal opioid misuse prevention programs like the Prescription Drug Monitoring Program.…”
Section: Introductionmentioning
confidence: 99%
“…8 Although several studies have examined opioid usage following foot and ankle procedures, there is a paucity of data on risk factors for prolonged opioid usage following TAA. A recent prospective cohort study by Saini et al 17 identified 4 independent factors associated with increased opioid consumption following outpatient foot and ankle procedures: regional block anesthesia, age <60 years, preoperative visual analog scale score >6, hindfoot procedures, and bony procedures. In the same study, there was a trend toward patients who self-reported anxiety consuming greater opioids; however, it did not achieve statistical significance.…”
Section: Discussionmentioning
confidence: 99%
“…In the same study, there was a trend toward patients who self-reported anxiety consuming greater opioids; however, it did not achieve statistical significance. 17 Merrill et al 12 reported that patients undergoing ankle/hindfoot procedures consumed a significantly higher number of long-acting opioids, such as MS Contin or Oxycontin (Purdue Pharma), when compared to forefoot procedures. They found no difference in bony vs soft tissue procedures or in use of short-acting opioids.…”
Section: Discussionmentioning
confidence: 99%
“…Prescription opioids are commonly used to manage postoperative pain (Berterame et al, 2016; Morris & Mir, 2015; Neuman, Bateman, & Wunsch, 2019; Seymour, Ring, Higgins, & Hsu, 2017). However, recent studies have shown that postoperative discharge opioid prescriptions are frequently variable and more than what patients actually require for effective pain relief (Bicket, Long, Pronovost, Alexander, & Wu, 2017; Saini et al, 2018). Overprescription of opioids may lead to heightened risks of adverse events, opioid misuse, opioid dependence, diversion for nonmedical uses, overdose, and death (Morris & Mir, 2015; Seymour et al, 2017).…”
Section: Introductionmentioning
confidence: 99%